Viral Emerging Diseases: Challenges in Developing Vaccination Strategies - Trovato, Maria; Sartorius, Rossella; D’Apice, Luciana; Manco, Roberta; De Berardinis, Piergiuseppe (Frontiers in Immunology, 2020)
In the last decades, a number of infectious viruses have emerged from wildlife or re-emerged, generating serious threats to the global health and to the economy worldwide. Severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), Ebola and Marburg haemorrhagic fevers, Lassa fever, Dengue fever, Yellow fever, West Nile fever, Zika and Chikungunya vector-borne diseases, swine flu, and the recent Coronavirus disease 2019 (COVID-19), are examples of zoonoses that have spread throughout the globe with a such significant impact on the public health to call the scientific community for a rapid intervention in preventing and treating emerging infections. Vaccination is probably the most effective tool in helping the immune system to activate protective responses against pathogens, reducing morbidity and mortality, as proven by historical records. Under health emergency conditions, new and alternative approaches in vaccine design and development are imperative for a rapid and massive vaccination coverage, in order to manage a disease outbreak and curtail the epidemic spread. This review gives an update on the current vaccination strategies for some of the emerging/re-emerging viruses, and discusses challenges and hurdles to overcome for developing efficacious vaccines against future pathogens.